PROGRAMA AABB - UNIJUÍ-PREFEITURA MUNICIPAL: DA INTERAÇÃO COM O OUTRO A SIGNIFICAÇÃO DA CIDADANIA - MAI, CIBELE; SILVA, GLADIS T. N. D.; DECKMANN, NEUSA T.; MARTINI, TALITA G.; LIMA, ELAINE N. D.; BORGES, ROBSON M.; GOETTEMS, LISIANE; MACAGNAN, MARISTELA F.; BORGMANN, MARTA E. (Salão do Conhecimento, 2013)
Resumo